Validation of the American Orthopaedic Foot and Ankle Society Ankle-Hindfoot Scale Dutch language version in patients with hindfoot fractures. Issue 11 (14th November 2017) - De Boer, A Siebe; Meuffels, Duncan E; Van der Vlies, Cornelis H; Den Hoed, P Ted; Tuinebreijer, Wim E; Verhofstad, Michael H J; Van Lieshout, Esther M M
Abstract : Objectives: The American Orthopaedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot Scale is among the most used questionnaires for measuring functional recovery after a hindfoot injury. Recently, this instrument was translated and culturally adapted into a Dutch version. In this study, the measurement properties of the Dutch language version (DLV) were investigated in patients with a unilateral hindfoot fracture. Design: Multicentre, prospective observational study. Setting: This multicentre study was conducted in three Dutch hospitals. Participants: In total, 118 patients with a unilateral hindfoot fracture were included. Three patients were lost to follow-up. Primary and secondary outcome measures: Patients were asked to complete the AOFAS-DLV, the Foot Function Index and the Short Form-36 on three occasions. Descriptive statistics (including floor and ceiling effects), reliability (ie, internal consistency), construct validity, reproducibility (ie, test–retest reliability, agreement and smallest detectable change (SDC)) and responsiveness were determined. Results: Internal consistency was inadequate for the AOFAS-DLV total scale (α=0.585), but adequate for the function subscale (α=0.863). The questionnaire had adequate construct validity (82.4% of predefined hypotheses were confirmed), but inadequate longitudinal validity (70.6%). No floor effects were found, but ceiling effects were present in all AOFAS-DLV (sub)scales, most pronounced from 6 to 24 months after trauma onwards. Responsiveness was only adequate for the pain and alignment subscales, with a SDC of 1.7 points. Conclusions: The AOFAS Ankle-Hindfoot Scale DLV has adequate construct validity and is reliable, making it a suitable instrument for cross-sectional studies investigating functional outcome in patients with a hindfoot fracture. The inadequate longitudinal validity and responsiveness, however, hamper the use of the questionnaire in longitudinal studies and for assessing long-term functional outcome. Trial registration number: NTR5613 ; Post-results.